2019
DOI: 10.18203/2394-6040.ijcmph20193608
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of knowledge and practice regarding menstrual hygiene among private and government schools of Jaipur city

Abstract: Background: Menstruation is a normal physiological process to the females but sometimes it is considered as unclean phenomenon in the society. Hence this community based study was carried out with the objective to assess the difference in level of knowledge and practice regarding menstrual hygiene among school going adolescent girls of government and private school.Methods: A community-based cross-sectional study was conducted from July 2017 to April 2018 to find out the difference in prevailing knowledge and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 3 publications
1
4
1
Order By: Relevance
“…The hand wash was practiced after handling garbage and after handling animals by 88.1% and 72.3% [8] . In this study 68.2% students practiced for cutting nails which was lower than other studies [5][6]8] . but hair cutting practice was found better (82.6%).…”
Section: Discussioncontrasting
confidence: 61%
See 3 more Smart Citations
“…The hand wash was practiced after handling garbage and after handling animals by 88.1% and 72.3% [8] . In this study 68.2% students practiced for cutting nails which was lower than other studies [5][6]8] . but hair cutting practice was found better (82.6%).…”
Section: Discussioncontrasting
confidence: 61%
“…In present study more than 90% students had knowledge about body and clothes hygiene, about teeth brushing, about regular clothes washing, 87.9% had knowledge about soap use in personal hygiene, 46.3% had knowledge about use of toilet paper, 72.6% had knowledge about use of nail cutter and 29.8% knowledge about sanitary pad. A study conducted in Jaipur reported almost similar finding regarding knowledge about body, teeth, clothes hygiene and use of soap but knowledge about sanitary pad was more (37.1%) compared to present study [5] . A study in Ethiopia country reported that majority of the students (99.7% and 85.7%) had knowledge of hand washing before and after meals while only 75% of students felt need of hand washing after defecation [10] .…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…15 The study by Sihra et al showed that 37.1% girls had knowledge about sanitary pad while in the present study, 97% girls had knowledge about sanitary pads as the girls in this study covered class from VIII and above. 14 Besides, such pads are made available to needed students from school itself these days. In this study 88 (35.20%) students were found using toothpaste for brushing the teeth, however the remaining were found using other materials such as neem stick, charcoal for brushing the teeth.…”
Section: Discussionmentioning
confidence: 99%